2018
DOI: 10.1371/journal.pone.0203017
|View full text |Cite
|
Sign up to set email alerts
|

Quality and resource efficiency in hospital service provision: A geoadditive stochastic frontier analysis of stroke quality of care in Germany

Abstract: We specify a Bayesian, geoadditive Stochastic Frontier Analysis (SFA) model to assess hospital performance along the dimensions of resources and quality of stroke care in German hospitals. With 1,100 annual observations and data from 2006 to 2013 and risk-adjusted patient volume as output, we introduce a production function that captures quality, resource inputs, hospital inefficiency determinants and spatial patterns of inefficiencies. With high relevance for hospital management and health system regulators, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 92 publications
0
13
0
1
Order By: Relevance
“…By providing the participating hospitals with improvement consultation, workshops, and webinars based on guidelines, GWTG-Stroke program achieved significant improvement of composite measure of care from 83.53 to 93.97% [25]. Data analysis from 2010 to 2013 in Germany showed that the mortality was reduced by up to 6.26 (63.7%) deaths per year, if the average hospital boosts its performance to an efficient treatment of stroke patients [26]. In CASE trial, the automated calculation of KPIs identifies the non-compliance of guideline-based care, which allows the clinicians to examine their cause and develop programs to decrease their frequency.…”
Section: Discussionmentioning
confidence: 99%
“…By providing the participating hospitals with improvement consultation, workshops, and webinars based on guidelines, GWTG-Stroke program achieved significant improvement of composite measure of care from 83.53 to 93.97% [25]. Data analysis from 2010 to 2013 in Germany showed that the mortality was reduced by up to 6.26 (63.7%) deaths per year, if the average hospital boosts its performance to an efficient treatment of stroke patients [26]. In CASE trial, the automated calculation of KPIs identifies the non-compliance of guideline-based care, which allows the clinicians to examine their cause and develop programs to decrease their frequency.…”
Section: Discussionmentioning
confidence: 99%
“…By providing the participating hospitals with improvement consultation, workshops, and webinars based on guidelines, GWTG-Stroke program achieved signi cant improvement of composite measure of care from 83.53% to 93.97% (25) . Data analysis from 2010 to 2013 in Germany showed that the mortality was reduced by up to 6.26 (63.7%) deaths per year, if the average hospital boosts its performance to an e cient treatment of stroke patients (26) . In CASE trial, the automated calculation of KPIs identi es the non-compliance of guideline-based care, which allows the clinicians to examine their cause and develop programs to decrease their frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Rumah sakit harus mengoptimalkan hubungan antara biaya dan kualitas pelayanan kesehatan yang seimbang agar efisiensi dapat terjadi. 15 Salah satu upaya guna meningkatkan efisiensi ialah rumah sakit harus memiliki clinical pathway untuk setiap diagnosis penyakit sebagai sebuah acuan dalam memberikan pelayanan medis pada pasien. 16 Acuan pelayanan medis yang digunakan oleh RSUD Panembahan Senopati ialah Standar Pelayanan Medis (SPM), namun terdapat dua jenis penyakit yang tidak memiliki SPM tentang penatalaksanaan pengobatannya, yaitu hipertensi dan diabetes melitus.…”
Section: Pembahasanunclassified